Graph Drawing in Motion - Friedrich, Carsten; Eades, Peter (Journal of Graph Algorithms and Applications, 2002)
Enabling the user of a graph drawing system to preserve the mental map between two different layouts of a graph is a major problem. In this paper we present methods that smoothly transform one drawing of a graph into another without any restrictions to the class of graphs or type of layout algorithm. <!—->